UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DI MAN 4 PASAMAN BARAT - HARMEN HARIANTO (STKIP Pesisir Selatan, 2019)
Based on observations that researchers have conducted teachers at MAN 4 Pasaman Barat, it was found that the ability of teachers to improve teacher pedagogical competence is still low. The purpose of this study is to describe and obtain information about improving teacher pedagogical competence. This research is a madrasa action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 8 teachers from MAN 4 Pasaman Barat. Research data were collected using observation sheets. Data were analyzed using percentages. The results showed that with academic supervision the teacher pedagogical competence at MAN 4 Pasaman Barat. This was proven by the existence of Academic supervision that could improve teacher pedagogical competence at MAN 4 Pasaman Barat from cycle I to cycle II. The average teacher's ability to improve the making of lesson plans in the first cycle was 51.30 with less categories, in the second cycle was 84.47 Good.